Sprint interval climbing increases anaerobic training load in elite female +78 kg judo athletes - Huang, Liying; Yao, Hu; Weng, Xiquan; Chen, Hao (Frontiers in Sports and Active Living, 2025)
IntroductionThe decisive movements that determine judo performance rely on anaerobic power. Currently, the optimum training protocol for increasing the anaerobic endurance of heavyweight judo athletes remains elusive due to tricky balance between training loads increase and injury prevention. This study investigated the impact of sprint interval climbing incorporated into the regular training on the anaerobic training load of heavyweight judo athletes.MethodsFive judo athletes of the female +78 kg category from the Chinese national team (average age: 26.8 ± 2.8 years; height: 185.6 ± 5.7 cm; weight: 127.8 ± 5.8 kg; judo training experience: 15 ± 3.5 years) conducted only regular training from October to December 2019 while climbing training was added to regular training from January to March 2020. A climbing fitness test was performed once per month from January to March 2020. The anaerobic training loads in the training and simulated matches were monitored through blood lactate and heart rate metrics, the physical fitness of the subjects was monitored through blood metrics such as creatine kinase, and the internal load of the subjects was assessed using Omegawave Technology readiness scores.ResultsWe found that sprint interval climbing increased the levels of blood lactate (P = 0.00) and heart rate metrics (P = 0.00) in the training and/or simulated matches and the performance in the fitness tests. Meanwhile, physiological parameters and the internal load remained comparable before and after climbing training.ConclusionsThese results suggested that sprint interval climbing increased anaerobic training load without obvious muscular damage or fitness decrease. Finally, lack of a control group due to limited availability of the subjects meeting the criteria and the need to maximize the performance of each subject in future matches was the major limitation of this study.